The Evangelicals: the struggle to shape America - FitzGerald, Frances (Simon & Schuster, 2017)
The great awakenings and the Evangelical empire -- Liberals and conservatives in the Post-Civil War North -- The fundamentalist-modernist conflict -- The separatists -- Billy Graham and modern evangelicalism -- Pentecostals and Southern Baptists -- Evangelicals in the sixties -- The fundamentalist uprising in the South -- Jerry Falwell and he moral majority -- Reagan and the South turns Republican -- The Evangelical thinkers -- Pat Robertson : politics and charismatic prophecies -- The Christian coalition and the Republican Party -- The Christian right and George W. Bush -- New Evangelicals -- The transformation of the Christian right